If m is 1 and q is 5, then our expression becomes
simplifying this gets us
Similarly, if x = 1 and y = 3, then the expression (y - x) 3 becomes
which simplifies to
Hence, the answer to our second expression is 6.
Now for the third expression.
putting in p = 4 and q = 3 in q (p+2) gives us
3 * (4 + 2)
which gives us
3 * 6 = 18.
Hence, the third expression evaluates to 18.
The fourth expression. We put in x = 6 and y = 5 into y + y - x to get
5 + 5 - 6 = 4
The fourth expression evaluates to 4.
The fifth expression. We put in y = 6 and z = 6 in (z+ y) ÷ 6 to get
(6 + 6) ÷ 6 = 12 ÷ 6 = 2
Hence, the fifth expression evaluates to 2.
Now for the sixth and the last expression.
We put in h = 3 and j = 6 into h(j - h) and we get
3*(6 - 3) = 3* 3 = 9
Hence, the sixth expression evalautes to 9.